RISK FACTORS FOR FEMALE INFERTILITY AT A TERTIARY HEALTH FACILITY IN AKURE, SOUTH-WEST NIGERIA - Irinyenikan, T. A. (International Journal of Medicine and Medical Research, 2020)
Background. The inability of couples to achieve pregnancy is a major cause of psycho-social problems in family relationship that could lead to marital disharmony. Objective. The aim of this study was to find out the possible risk factors for female infertility. Methods. A case-control design and a sample size of 400 (200 cases of infertility and 200 controls) were used in the study. Cases and controls were selected at random at the infertility and family planning clinic of the University of Medical Sciences Teaching Hospital Complex, Akure and were subjected to a predesigned interviewer administered questionnaire to collect the data. The cases were classified into primary and secondary infertility; binary and stepwise logistic regressions were used to generate the Odds ratio and 95% confidence interval of the possible risk factors and the level of significance was set at P<0.05. Results. The mean age of the women with infertility was 28.5±5.43 years and the mean age of those in the control group was 29.1±5.62 years. Among the cases, 155 (77.5%) had secondary infertility, while 45 (22.5%) had primary infertility. Significant risk factors for female infertility included presence of fibroids, having had fibroid operation, multiple sexual partners, previous abortion, polycystic ovary syndrome (PCOS), sexually transmitted infection (STI) and post abortion sepsis. Conclusion. The study showed that secondary infertility is still the most prevalent and the risk factors were multi factorial. Efforts should be intensified to reduce infertility due to preventable causes.